Improvement of Phenol Degradation by UV Irradiation on Ultrasonic Atomized Droplets - Daisuke Kobayashi; Hinano Watanabe (Chemical Engineering Transactions)
Photocatalysis such as TiO2 particles are expected to be applied to the degradation of hazardous organic materials as an advanced oxidation processes (AOPs). However, UV light is shielded by the catalyst particles, so the area of catalytic activity is limited spatially. On the other hand, ultrasonic atomization has been reported to produce very fine droplets from bulk solutions, and to disperse particles in liquids into droplets. Therefore, it is expected that the combination of ultrasonic atomization and photocatalysis enables a higher concentration of photocatalytic particles in the atomized droplets. In this study, droplets containing TiO2 were generated using an ultrasonic atomizer, and phenol degradation was carried out by UV light irradiation to the droplets. Kinetic analysis was performed by assuming the reaction to be a pseudo-first-order reaction, and the effects of particle concentration and particle size on the degradation rate constants were investigated. The degradation rate constant increased with increasing TiO2 particle addition. Phenol degradation by photocatalytic particles and UV irradiation was also investigated. The results were compared with those obtained with a device that uses a combination of ultrasonic atomization and UV irradiation. At the same TiO2 particle concentration, the degradation rate of the device that combined ultrasonic atomization and UV irradiation was higher than that of the device that used UV irradiation. It is assumed that the equipment using a combination of ultrasonic atomization and UV irradiation increased the degradation rate because TiO2 particles were concentrated and incorporated into the droplets, resulting in a higher particle concentration. It is estimated that TiO2 particle concentration inside the droplet is twice as concentrated as evaluated from the results of degradation rate constant.